2014
DOI: 10.1155/2014/494695
|View full text |Cite
|
Sign up to set email alerts
|

Does Postevacuation β-Human Chorionic Gonadotropin Level Predict the Persistent Gestational Trophoblastic Neoplasia?

Abstract: β-human chorionic gonadotropin (HCG) level is not a reliable marker for early identification of persistent gestational trophoblastic neoplasia (GTN) after evacuation of hydatidiform mole. Thus, this study was conducted to evaluate β-HCG regression after evacuation as a predictive factor of malignant GTN in complete molar pregnancy. Methods. In this cross-sectional study, we evaluated a total of 260 patients with complete molar pregnancy. Sixteen of the 260 patients were excluded. Serum levels of HCG were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Consistent with our finding previous studies showed that β-hCG measurement after treated a molar pregnancy is a good marker to differentiate patients who will get spontaneous recovery from patients developing GTN. [ 7 20 21 22 ] A study on 3926 women with partial or complete mole showed that risk of GTN was clearly different based on the levels of β-hCG and rising with β-hCG level. [ 2 ] In another study more than 50% of patients who will really develop GTN can be predicted using the slope of the regression line of β-hCG with 97.5% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding previous studies showed that β-hCG measurement after treated a molar pregnancy is a good marker to differentiate patients who will get spontaneous recovery from patients developing GTN. [ 7 20 21 22 ] A study on 3926 women with partial or complete mole showed that risk of GTN was clearly different based on the levels of β-hCG and rising with β-hCG level. [ 2 ] In another study more than 50% of patients who will really develop GTN can be predicted using the slope of the regression line of β-hCG with 97.5% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Although these tools can be helpful as a reference guideline, they will not provide an individualized risk estimate. Other authors divided serum hCG measurements in two categories to predict risk of post-molar GTN [39,40]. A possible limitation of these studies lies in the reduction of serum hCG measurements in categories, whereas the association between serum hCG and post-molar GTN should probably be considered as a continuous scale [39,40].…”
Section: Risk Of Progression To Post-molar Gtnmentioning
confidence: 99%
“…Other authors divided serum hCG measurements in two categories to predict risk of post-molar GTN [39,40]. A possible limitation of these studies lies in the reduction of serum hCG measurements in categories, whereas the association between serum hCG and post-molar GTN should probably be considered as a continuous scale [39,40]. In a study of Dandis et al [41], hCG levels available between week 1 to 4 after evacuation of the molar pregnancy were jointly used to predict the risk of progression to post-molar GTN.…”
Section: Risk Of Progression To Post-molar Gtnmentioning
confidence: 99%
“…Several studies discussed the challenge of predicting post–molar GTN based on either single hCG measurements or a summary measure like the decline rate that captures the change in hCG over time (Aminimoghaddam et al., ; Kim et al., ; Mousavi, Karimi, Modarres Gilani, Akhavan, & Rezayof, ). Eysbouts et al.…”
Section: Example Data Setmentioning
confidence: 99%
“…Several studies discussed the challenge of predicting post-molar GTN based on either single hCG measurements or a summary measure like the decline rate that captures the change in hCG over time (Aminimoghaddam et al, 2014;Kim et al, 2012;Mousavi, Karimi, Modarres Gilani, Akhavan, & Rezayof, 2014). Eysbouts et al developed a practical and easy tool to obtain subject-specific risk predictions of post-molar GTN for each of the first four weeks after evacuation, based on serum hCG (Eysbouts, Massuger, Ottevanger, IntHout, & Sweep, 2017).…”
Section: Example Data Setmentioning
confidence: 99%